7th International Congress of Child and Adolescent Psychiatry - IJABS, International Journals IJABS (International Journal of Applied Behavioral Sciences, 2015)
The 7th International Congress of Child and Adolescent Psychiatry 12-14 May 2015, Tehran, Iran Shahid Beheshti University of Medical Sciences, Tehran Conference Theme: Violence Prevention and Promotion of Mental Health Head of Congress: Mehdi Tehrani-Doost, M.D Scientific Secretary: Rozita Davari Ashtiani, M.D Executive Secretary: Katayoun Razjouyan, M.D Executive Manager: Fahima Farrahi The Scientific Committee: Nasrin Sarraf, Arsia Taghva, Sorur Arman, Mohammad reza Eslami, Mahin Eslami, Taghi esmaeeli, Soheila Emami, Shahrokh Amiri, Nasrin Amiri, Houshang Amirian, Mehdi Bina, Noushin Parvaresh, Ashraf Tashakori, Reza Tavakolian, Mehdi Tehrani doost, Seyed Ahmad Jalili, Behrouz Jalili, Mitra Joudi, Paria Hebrani, Nastaran Habibi, Shahram Heidari, Katayoun ,Khoushabi, Rozita Davari Ashtiani, Firouzeh Derakhshanpour, Nasrin Dodangi, Shokoufeh Radfar Katayoun Razjouyan, Forough Riahi, Ghazal Zahed, Elham Salari, Zahra Sepehrmanrsh, Atefeh Soltanifar, Hassan Shahrokhi, Arefeh Shefaat, Fereshteh Shakibaee, Mitra Hakim Shoshtari, Zahra Shahrivar, Elham Shirazi, Ali Alavi shooshtari, Mohammadali Sahebi, Afsaneh Sehat, Seyed Saeed Sadr, Mohammadreza Sadrameli, Nasrin Saraf, Parvin Safavi, Alireza Zahiroldin, Abdolahian, Fariba Arabgol, Fatemeh Asarian, Abbas Attari, Anita Alaghmand, Mohammad Effatpanah, Marzieh ,Assareh, Javad Alaghbandrad, Ahmad Ghanizadeh, Hossein Faker, Mahboobeh Firuzkuhi Mohammadreza Kazemi, Afsaneh Karbasi Amel, Arezou Kiani, Maryam Kipour, Ayub Malek, Fatemeh Mohareri, Mohammadreza Mohammadi, Mehrdad Mohammadian, Maryam Mahmoudirad, Javad ,Mahmoudi Gharaee, Azadeh Mazaheri, Shirin Moalemi, Shokufeh Mousavi, Masoumeh Mousavi Parviz Molavi, Niloufar Mahdavi, Javad Golmirzaee, Mostafa Najafi, Gholamreza Noourazar, Peyman Hashemian, Hamid Yaghubi, Maryam Kousha The Executive Committee: Mehdi Tehranidoost, Katayoun Razjouyan, Zahra Shahrivar, Javad ,Golmirzaee, Javad Mahmoudi Gharaee,Fahima Farrahi, Mojgan Khademi, Firouzeh Jafari ,Mohammadreza Eslami, Mohammad Amin Sattari, Shokoufeh Saffari, Azadeh Sadat Kheradmand Nahid Borna, Anahita Rezaee, Fatemeh Gholipour, Afshin Soleimanpour, Fahima Farrahi, Maziar ,Malekpour, Gilda Rajabi ,Damavandi, Hedie Farrahi, Hamed Mazaheri, Sina Zarrini, Helia Tarighatnia Mahya Seyed Safizadeh, Samira Sadeghi Parvin, Masoumeh Fadavi, Shadi Ansari, Hengameh Hosseini, Farzad Kashefi, Amirali Fadavi, Maziar Malekpoor, Elmira Bonyadi, Ashkan Abolhalaj